In vitro susceptibility of Mycobacterium abscessus complex and feasibility of standardizing treatment regimens. (18th December 2020) - Chew, Ka Lip; Octavia, Sophie; Go, Joelle; Ng, Sally; Tang, Yit Er; Soh, Patsy; Yong, Joy; Jureen, Roland; Lin, Raymond Tzer Pin; Yeoh, Siang Fei; Teo, Jeanette
Abstract: Objectives: To determine the in vitro susceptibility of members of the Mycobacterium abscessus complex to routinely tested antibiotics and to an extended antibiotic panel. Methods: Non-duplicate isolates for which susceptibility testing results were available were included in this study. Retrospective laboratory records were reviewed, including tigecycline susceptibility results, and testing was performed with additional drugs, including vancomycin, dalbavancin, telavancin, oritavancin, rifabutin, delafloxacin, eravacycline, clofazimine and bedaquiline using broth microdilution (Sensititre, Thermo Fisher). Results: A total of 218 M. abscessus complex isolates were included for retrospective review, of which 151 were respiratory isolates. Of these 218 isolates, 211 were available for additional testing with the extended antibiotic panel. Of these, 146 were respiratory isolates. One isolate had a vancomycin MIC of 2 mg/L and MICs of all other isolates were >8 mg/L. All isolates had MICs of >8 mg/L for oritavancin, dalbavancin and telavancin. One isolate had a delafloxacin MIC of 4 mg/L and MICs of all other isolates were >8 mg/L. The MIC50 /MIC90 s of rifabutin, tigecycline, eravacycline, clofazimine and bedaquiline were 16/32, 0.5/1, 0.12/0.25, 0.12/0.25 and 0.06/0.12 mg/L, respectively. Conclusions: In vitro activity was demonstrated for clofazimine, bedaquiline and eravacycline, indicating potential for inclusion as standardized therapy for M. abscessus complex infections.